Influence of twin boundaries and sample dimensions on the mechanical behavior of Ag nanowires - Zhao, H.; Yılmaz, Halil; Williams, C.J.; Eggeman, A.S.; Derby, B. (Elsevier Ltd, 2022)
The tensile mechanical properties of silver nanowires produced by the polyol process and containing the characteristic pentatwinned microstructure are compared with single crystal nanowires prepared by template electrodeposition over a range of diameters, d, from 80 to 300 nm. The plastic flow strengths of both sets of nanowires show a significant size effect, ranging from about 400 MPa at d ? 300 nm to in excess of 1 GPa with d < 100 nm. The size effect is shown to follow the same empirical scaling law seen with other fcc structured metals. Transmission electron microscopy investigation of the deformed specimens found similar deformation structures in both classes of nanowire studied with relatively low dislocation densities found even after significant plastic strain. The deformed pentatwinned nanowires showed no evidence for any characteristic deformation structures associated with the twin boundaries running parallel to the nanowire axis. © 2021 Elsevier B.V.
Keywords: Ag nanowires; Electron microscopy; Size effect; Twinning; Deformation; High resolution transmission electron microscopy; Single crystals; Size determination; Twinning; Ag nanowires; Deformation structure; Empirical scaling; Flow strength; Mechanical behavior; Polyol process; Single crystal nanowires; Sizes effect; Tensile mechanical properties; Twin boundaries; Nanowires